Training in the use of intrapartum electronic fetal monitoring with cardiotocography: systematic review and meta‐analysis. (22nd January 2021) - Kelly, S; Redmond, P; King, S; Oliver‐Williams, C; Lamé, G; Liberati, E; Kuhn, I; Winter, C; Draycott, T; Dixon‐Woods, M; Burt, J
Abstract : Background: Sub‐optimal classification, interpretation and response to intrapartum electronic fetal monitoring using cardiotocography are known problems. Training is often recommended as a solution, but there is lack of clarity about the effects of training and which type of training works best. Objectives: Systematic review of the effects of training healthcare professionals in intrapartum cardiotocography (PROSPERO protocol: CRD42017064525). Search strategy: CENTRAL, Cochrane Library, MEDLINE, EMBASE, PsycINFO, British Nursing Database, CINAHL, ERIC, Scopus, Web of Science, ProQuest, grey literature and ongoing clinical trials were searched. Selection criteria: Primary studies that reported impact of training healthcare professionals in intrapartum cardiotocography. Title/abstract, full‐text screening and quality assessment were conducted in duplicate. Data collection and analysis: Data were synthesised both narratively and using meta‐analysis. Risk of bias and overall quality were assessed with the Mixed Methods Appraisal Tool and GRADE. Main results: Sixty‐four studies were included. Overall, training and reporting were heterogeneous, the outcomes evaluated varied widely and study quality was low. Five randomised controlled trials reported that training improved knowledge of maternity professionals compared with no training, but evidence was of low quality. Evidence for the impact of cardiotocography training on neonatal and maternal outcomes was limited, showed inconsistent effects, and was of low overall quality. Evidence for the optimal content and method of delivery of training was very limited. Conclusions: Given the scale of harm and litigation claims associated with electronic fetal monitoring, the evidence‐base for training requires improvement. It should address intervention design, evaluation of clinical outcomes and system‐wide contexts of sub‐optimal practice. Tweetable abstract: Training in fetal monitoring: systematic review finds little evidence of impact on neonatal outcomes. Tweetable abstract: Training in fetal monitoring: systematic review finds little evidence of impact on neonatal outcomes.